2007
DOI: 10.1007/s00420-007-0193-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of biomarkers of occupational exposure to toluene

Abstract: In over-all evaluation, hippuric acid, followed by un-metabolized toluene and omicron-cresol, is the marker of choice for occupational toluene exposure. When toluene exposure level is low (e.g., 2 ppm), un-metabolized toluene and benzylmercapturic acid in urine may be better indicators. Detection of un-metabolized toluene or benzylmercapturic acid in urine at the levels in excess of the LODs may be taken as a positive evidence of toluene exposure, because their levels in urine from the controls are below the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 40 publications
3
31
3
1
Order By: Relevance
“…The correlation of o-CR-U ob was less significant with r=0.20 and p<0.05, whereas BeOH-U ob and BMA-U ob did not correlate significantly (r=0.16 and 0.11, respectively, with p>0.10 for both; Table 3). In the two previous studies, one 10) with toluene exposure at moderate levels (at 10 ppm as GM and at 121 ppm as the maximum) and the other 11) at low levels (at 1.6 ppm as GM and 26.5 ppm as the maximum), Tol-U correlated with TWA toluene concentrations in air not only at moderate levels but at low levels. No Tol-B was examined in the moderate exposure study 10) , but separate studies showed that Tol-B significantly correlates with air-borne toluene at low levels 11) as well as at high levels (the maximum level being 132 ppm) 23 Abbreviations are: BeOH-U, benzyl alcohol in urine; BMA-U, benzylmercapturic acid in urine; o-CR, o-cresol in urine; HA-U, hippuric acid in urine; Tol-U, toluene in urine and Tol-B, toluene in blood.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The correlation of o-CR-U ob was less significant with r=0.20 and p<0.05, whereas BeOH-U ob and BMA-U ob did not correlate significantly (r=0.16 and 0.11, respectively, with p>0.10 for both; Table 3). In the two previous studies, one 10) with toluene exposure at moderate levels (at 10 ppm as GM and at 121 ppm as the maximum) and the other 11) at low levels (at 1.6 ppm as GM and 26.5 ppm as the maximum), Tol-U correlated with TWA toluene concentrations in air not only at moderate levels but at low levels. No Tol-B was examined in the moderate exposure study 10) , but separate studies showed that Tol-B significantly correlates with air-borne toluene at low levels 11) as well as at high levels (the maximum level being 132 ppm) 23 Abbreviations are: BeOH-U, benzyl alcohol in urine; BMA-U, benzylmercapturic acid in urine; o-CR, o-cresol in urine; HA-U, hippuric acid in urine; Tol-U, toluene in urine and Tol-B, toluene in blood.…”
Section: Discussionmentioning
confidence: 72%
“…A close correlation (r=0.80) with toluene in air was reported for BeOH-U ob in a factory survey in which workers were exposed to toluene at 12.6 ppm and 130 ppm as the maximum 11) . Similarly, the correlation was high when toluene exposure was intense (i.e., 15 ppm as GM and 70 ppm as the maximum), but it was substantially less close otherwise 10) . Thus, the present observation of low correlation (r=0.16 with p>0.10) is on line with the previous observation of poor correlation when toluene exposure was low 10) .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The use was not limited to occupational health where the method was originally developed [1][2][3][4][5][6] , but also in environmental health fields 7,8) . The method has been applied to analysis for un-metabolized mother chemicals 1,[9][10][11][12] as well as for metabolites after proper automated derivatization of metabolites to increase volatility [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%